The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1080/09658210244000298
|View full text |Cite
|
Sign up to set email alerts
|

Implicit word activation during pre‐recognition processing influences correct recognition and estimates of presentation frequency

Abstract: False recognition of new test words is higher for experimental lures (e.g., universal) with initial phonemes identical to studied words (e.g., university) than for control lures. A proposed mechanism to explain this phenomenon involves implicit activation of potential solution words during the brief period of uncertainty immediately following onset of a spoken study word. Two experiments examined whether the presumed pre-recognition processing during the stimulus discovery phase of spoken word identification i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…After hearing such a list, listeners falsely remembered the unheard word back on average 65 to 70% of the time (Sommers & Lewis 1999). Several studies have reported similar results, for both serial recall and yes/no recognition tasks, and established the robustness of false phonological memories (Wallace, Stewart & Malone 1995;Schacter, Verfaellie & Anes 1997;Wallace et al 1998;Wallace et al 2001;Westbury, Buchanan & Brown 2002;Watson, Balota & Roediger 2003;Amberg, Yamashita & Wallace 2004;Garoff-Eaton, Kensinger & Schacter 2007;Ballardini, Yamashita & Wallace 2008;Ballou & Sommers 2008). In our study, we asked participants to listen to lists of neighbors such as popa, sepa, soja, etc.…”
Section: Introductionmentioning
confidence: 52%
“…After hearing such a list, listeners falsely remembered the unheard word back on average 65 to 70% of the time (Sommers & Lewis 1999). Several studies have reported similar results, for both serial recall and yes/no recognition tasks, and established the robustness of false phonological memories (Wallace, Stewart & Malone 1995;Schacter, Verfaellie & Anes 1997;Wallace et al 1998;Wallace et al 2001;Westbury, Buchanan & Brown 2002;Watson, Balota & Roediger 2003;Amberg, Yamashita & Wallace 2004;Garoff-Eaton, Kensinger & Schacter 2007;Ballardini, Yamashita & Wallace 2008;Ballou & Sommers 2008). In our study, we asked participants to listen to lists of neighbors such as popa, sepa, soja, etc.…”
Section: Introductionmentioning
confidence: 52%